Targeting lymphatic function in cardiovascular-kidney-metabolic syndrome: preclinical methods to analyze lymphatic function and therapeutic opportunities - Fowler, Joseph Wayne M.; Song, LouJin; Tam, Kelly; Roth Flach, Rachel J. (Frontiers in Cardiovascular Medicine, 2024)
The lymphatic vascular system spans nearly every organ in the body and serves as an important network that maintains fluid, metabolite, and immune cell homeostasis. Recently, there has been a growing interest in the role of lymphatic biology in chronic disorders outside the realm of lymphatic abnormalities, lymphedema, or oncology, such as cardiovascular-kidney-metabolic syndrome (CKM). We propose that enhancing lymphatic function pharmacologically may be a novel and effective way to improve quality of life in patients with CKM syndrome by engaging multiple pathologies at once throughout the body. Several promising therapeutic targets that enhance lymphatic function have already been reported and may have clinical benefit. However, much remains unclear of the discreet ways the lymphatic vasculature interacts with CKM pathogenesis, and translation of these therapeutic targets to clinical development is challenging. Thus, the field must improve characterization of lymphatic function in preclinical mouse models of CKM syndrome to better understand molecular mechanisms of disease and uncover effective therapies.